CIZ1, a p21Cip1/Waf1‐interacting protein, functions as a tumor suppressor in vivo. Issue 10 (11th April 2013) - Nishibe, Rio; Watanabe, Wataru; Ueda, Takeshi; Yamasaki, Norimasa; Koller, Richard; Wolff, Linda; Honda, Zen-ichiro; Ohtsubo, Motoaki; Honda, Hiroaki
Abstract : CIZ1 is a nuclear protein involved in DNA replication and is also implicated in human diseases including cancers. To gain an insight into its function in vivo, we generated mice lacking Ciz1 . Ciz1 ‐deficient ( Ciz1 −/− ) mice grew without any obvious abnormalities, and Ciz1 −/− mouse embryonic fibroblasts (MEFs) did not show any defects in cell cycle status, cell growth, and DNA damage response. However, Ciz1 −/− MEFs were sensitive to hydroxyurea‐mediated replication stress and susceptible to oncogene‐induced cellular transformation. In addition, Ciz1 −/− mice developed various types of leukemias by retroviral insertional mutagenesis. These results indicate that CIZ1 functions as a tumor suppressor in vivo. Abstract : Ciz1 ‐deficient ( Ciz1 −/− ) mouse embryonic fibroblasts (MEFs) did not show defects in cell cycle status, cell growth, and DNA damage response. Ciz1 −/− MEFs were sensitive to replication stress and susceptible to cellular transformation. Ciz1 −/− mice developed leukemias by retroviral insertional mutagenesis. CIZ1 functions as a tumor suppressor in vivo.